Rent taxation for nonrenewable resources - Diderik Lund (University of Oslo, Department of Economics, 2009)
The literature on taxation of rents from nonrenewable resources uses different theoretical assumptions and methods and a variety of empirical observations to arrive at widely diverging conclusions. Many studies use models and methods which disregard uncertainty, investigating distortionary effects of different taxes on whether, when, and how to explore for, develop and operate resource deposits. Introducing uncertainty into the analysis opens a range of challenges, and leads to results which cast doubt upon the relevance of studies which neglect uncertainty. There are, however, several ways to analyze uncertainty, regarding companies' behavior, resource price processes, and diversification opportunities, all with different implications for taxation. Methods developed in financial economics since the 1980's are promising, but still not in widespread use. Some more specific topics covered in this review are optimal risk sharing between companies and governments, time consistency and fiscal stability, the relationship between taxes and discount rates, and transfer pricing.
Keywords: B20; H20; H25; L71; O13; Q38; 330; natural resources; rent tax; royalty; oil; minerals; energy; Rohstoffsteuer; Erschöpfbare Ressourcen; Risiko; Hotelling-Regel; Theorie